CLIMATE AS A DETERMINANT OF HUMAN SETTLEMENT PATTERNS: A MULTISCALE ANALYSIS OF ENVIRONMENTAL INFLUENCE ON HABITATION AND MIGRATION - Pushpender (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study investigates the pivotal role of climate in shaping human settlement patterns across local, regional, and global scales. Utilizing a combination of spatial analysis, remote sensing data, and statistical correlation techniques, the research explores how climatic variables—such as temperature and rainfall—affect settlement density and migration trends. The findings reveal a strong positive correlation between moderate climatic conditions and high settlement density, particularly in temperate and subtropical regions. In contrast, areas experiencing climatic extremes—such as arid zones, flood-prone deltas, and polar environments—tend to have sparse populations or rely on extensive adaptive strategies. The study further highlights that climate change is not only altering the physical habitability of certain regions but is also driving significant migration flows, especially in environmentally vulnerable zones such as South Asia, Sub-Saharan Africa, and coastal lowlands. These migration patterns reflect both forced displacement due to environmental stress and strategic relocation aimed at minimizing climate-related risks. Beyond environmental determinism, the research underscores the importance of socio-economic, cultural, and institutional factors that mediate human responses to climate pressures. The findings carry important implications for urban planning, climate adaptation policy, and disaster risk reduction, emphasizing the need for integrated, climate-sensitive development strategies. By bridging geographical theory with empirical climate data, this study contributes to a deeper understanding of how environmental variables influence human behavior and spatial organization, offering a valuable framework for future research and policymaking in the context of global climate change.